Pendidikan Agama bagi Perempuan Perspektif Feminisme Islam (Analisis Kritis terhadap Kitab Tarbiyat al-Mar’ah wa al-Ḥijāb) - Elok Maulidah; Mahmutarom Mahmutarom; Sari Hernawati; Faizal Faithy Ersady (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2025)
Women's access to religious education remains a central issue in Islamic society, often influenced by patriarchal interpretations of religion. This research critically examines the book Tarbiyat al-Mar'ah wa al-Ḥijāb by Muḥammad Ṭalʿat Ḥarb to analyze the construction of women's religious education in early 20th-century Islamic thought. This research employs a qualitative approach with critical hermeneutics and an Islamic feminist framework referencing the ideas of Amina Wadud, Asma Barlas, and Fatima Mernissi. The study results show that although the text emphasizes the importance of religious education for women, the narrative constructed still limits women to domestic roles and reinforces gender hierarchies with religious legitimacy. This construction reflects a conservative response to modernity, emphasizing moral control over the empowerment of women's intellectual and social agency. This research confirms that religious education should not be a tool for domestication, but rather a means of empowering women intellectually, spiritually, and socially. This study contributes to the development of gender-equitable Islamic educational discourse.